2017
DOI: 10.14423/smj.0000000000000693
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease in Pregnancy

Abstract: With the increasing prevalence of chronic kidney disease (CKD) worldwide, the number of pregnant women with various degrees of renal dysfunction is expected to increase. There is a bidirectional relation between CKD and pregnancy in which renal dysfunction negatively affects pregnancy outcomes, and the pregnancy can have a deleterious impact on various aspects of kidney disease. It has been shown that even mild renal dysfunction can increase considerably the risk of adverse maternal and fetal outcomes. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Koratala et al 13 found that kidney damage occurring during pregnancy was linked to adverse pregnancy outcomes. This study found that, in the pregnancy-related renal damage group, the foetal survival rate was 77.1%, which was comparable to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Koratala et al 13 found that kidney damage occurring during pregnancy was linked to adverse pregnancy outcomes. This study found that, in the pregnancy-related renal damage group, the foetal survival rate was 77.1%, which was comparable to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they should be pre-conceptionally counseled for the same. 2 Whereas, with CKD, maternal hypertension and proteinuria not only deteriorate the CKD stage but also act as independent risk factors for poor outcome of pregnancy. Patients with immunologic diseases and glomerulonephritis are at a higher risk of developing a pre-eclampsia like picture with hypertension and proteinuria; often difficult to differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent reviews on pregnancy in CKD showed that patients usually had different renal and pregnancy outcomes due to different types of primary renal diseases, CKD stages, the presence of HTN and proteinuria [27][28][29][30][31][32]. Patients with various diseases such as lupus nephropathy or diabetic nephropathy might have a higher incidence of renal and pregnancy complications [33][34][35][36][37][38][39], while those with other glomerular diseases, such as IgAN and minimal change disease, had limited disease-specific data to guide pregnancy counseling.…”
Section: Discussionmentioning
confidence: 99%